Total Quality Management in Higher Education Schools Between Theory and Practice - Khalid Alsarayra; Laila Alassaf (University of Science and Technology, Yemen, 2008)
Total Quality Management in Higher Education Schools Between Theory and Practice  Abstract This study aimed at investigating total quality management in higher education institutions. In order to achieve this objective, the researchers adopted the analytic- descriptive approach in data collection and interpretation. The study focused on the concept of T.Q.M and the benefits and the requirents of its adaptation in higher education institutions. The study focused on T.Q.M indicators, topics and some countries' experiences of its application. The study concludes with a number of recommendations highlighting the significance of the employment of T.Q.M in higher education institutions.